Правовий аналіз внесених на розгляд Верховної Ради України змін до Конституції України - Ковальчук, О. Б. (Видавництво Львівської політехніки, 2015)
Дослідження розглядає питання реформування Конституції України, проект закону України “Про внесення змін до Конституції України (щодо повноважень органів державної влади та місцевого самоврядування)”, внесеного Президентом України до Верховної Ради України у 2014 році, правового аналізу його основних положень та вироблення відповідних пропозицій щодо впровадження запропонованих змін. Исследование посвящено вопросам реформирования Конституции Украины, рассмотрению проекта закона Украины “О внесении изменений в Конституцию Украины (относительно полномочий органов государственной власти и местного самоуправления)”, внесенного Президентом Украины в Верховный Совет Украины в 2014 году, правового анализа его основных положений и выработки соответствующих предложений относительно внедрения предложенных изменений. Research is sanctified to the questions of reformation of Constitution of Ukraine, consideration of project of Law of Ukraine “About making alteration in Constitution of Ukraine (in relation to plenary powers of public and local self-government authorities)”, brought in by President of Ukraine in Supreme soviet of Ukraine in 2014, to the legal analysis him substantive provisions and to making of corresponding suggestions in relation to introduction of offer changes.
Правовой анализ внесенных на рассмотрение Верховного Совета Украины изменений к Конституции Украины
The legal analysis of the changes introduced Supreme Soviet of Ukraine in Constitution of Ukraine
Keywords: конституція; органи місцевого самоврядування; Президент; право; депутат; коаліція; конституция; органы местного самоуправления; Президент; право; депутат; коалиция; constitution; organs of local self-government; President; right; deputy; coalition